Highly sex specific gene expression in Jojoba - Bader Alsubaie; Ardashir Kharabian-Masouleh; Agnelo Furtado; Othman Al-Dossary; Ibrahim Al-Mssallem; Robert J. Henry (BMC Plant Biology, 2023)
Abstract Background Dioecious plants have male and female flowers on separate plants. Jojoba is a dioecious plant that is drought-tolerant and native to arid areas. The genome sequence of male and female plants was recently reported and revealed an X and Y chromosome system, with two large male-specific insertions in the Y chromosome. Results A total of 16,923 differentially expressed genes (DEG) were identified between the flowers of the male and female jojoba plants. This represented 40% of the annotated genes in the genome. Many genes, including those responsible for plant environmental responses and those encoding transcription factors (TFs), were specific to male or female reproductive organs. Genes involved in plant hormone metabolism were also found to be associated with flower and pollen development. A total of 8938 up-regulated and 7985 down-regulated genes were identified in comparison between male and female flowers, including many novel genes specific to the jojoba plant. The most differentially expressed genes were associated with reproductive organ development. The highest number of DEG were linked with the Y chromosome in male plants. The male specific parts of the Y chromosome encoded 12 very highly expressed genes including 9 novel genes and 3 known genes associated with TFs and a plant hormone which may play an important role in flower development. Conclusion Many genes, largely with unknown functions, may explain the sexual dimorphisms in jojoba plants and the differentiation of male and female flowers.